Thesis Writing in MBS: Procedures and Practices (Journal of Nepalese Business Studies, 2006)
This paper has been prepared with an objective to provide the official guidelines to the MBS students to write the thesis and prepare the project work assignment, and teachers to guide their students in writing the thesis and preparing the project work assignment. So, this paper has included formats of thesis and project work assignment prescribed by Office of the Dean, Faculty of Management, Tribhuvan University and necessary procedures of the submission of thesis and project work assignment. Journal of Nepalese Business Studies Vol.1(1) 2004 pp.23-37